Pemberdayaan Masyarakat melalui Pelatihan Digital Marketing pada UMKM Produk Pertanian di Desa Bodag, Madiun, Jawa Timur - Adi, Prakoso; Mulyani, Rizka; Putri, Ardhiana Noor Hanifah; Saputri, Cindy Intan; Alfiyah, Hanin; Widyadana, Jalasena Reswara Arkananta; Ma’rifah, Khoirul; Khabibah, Lutfia Nur (Universitas Sebelas Maret, 2022)
Community Empowerment through Digital Marketing Training in Agricultural Product SMEs in Bodag Village, Madiun, East Java. Micro, Small and Medium Enterprises (MSMEs) are often faced with problems related to the limited range of product marketing because they only use conventional marketing. One of the solutions is through digital marketing to expand the reach of product marketing and increase product sales. This community service aims to provide knowledge and increase the interest of MSMEs in Bodag Village in developing technology-based businesses through digital marketing, as well as assisting MSMEs in Bodag Village in implementing digital marketing. Digital marketing training and assistance for MSMEs in Bodag Village have been carried out. The training was attended by SMEs Rumah Coklat Bodag, Kopi Laksana SMEs, Kopi Selo Gedong SMEs, Keripik Selo Gedong SMEs, Keripik Pop Krip, and Keripik Kiya. The training begins with increasing MSME knowledge and continues with hands-on practice. From the training results, MSMEs' knowledge of digital marketing has increased from a score of 45.79 to 76.84. Regarding skills, it also showed positive results with indicators of the ability of MSME members in Bodag Village to make catalogues of food products, as well as Instagram and website content for. Both of these are indicators of the successful implementation of this program. In addition, the interest in implementing digital marketing in the marketing process by MSMEs in Bodag Village also indicates that the implementation of the program has succeeded in fulfilling the purpose of doing community service.